ROLE OF WOMEN ENTREPRENEURS IN SOCIAL ENTREPRENEURSHIP - Rao, P.V.; KALYANI, H.A.L.N.S. (International Journal of Psychosocial Rehabilitation, 2019)
Entrepreneurship development is a buzzword which is attracting every person’s concern ingeneral and women in particular. The participation of women in entrepreneurship is significant and varies from nation to nation. It is observed that Indian Women are also participating in this trend. From a petty shop to a mega business magnet we find women are finding a space for themselves. Theynot only think of profits in their business venture but also are contributing to the development of society.